Geological and Geochemical Characteristics of the First Member of the Cretaceous Qingshankou Formation in the Qijia Sag, Northern Songliao Basin, Northeast China: Implication for Its Shale Oil Enrichment - Fei Xiao; Jianguo Yang; Shichao Li; Fanhao Gong; Jian Zhang; Yulai Yao; Ang Li; Liyan Zhang; Yiming Huang; Fei Su; Yunfeng Bai (Geofluids)
The Qijia Sag, a secondary tectonic unit in the northern Songliao Basin, developed plentiful shale oil resources in the first member of the Cretaceous Qingshankou Formation (K2qn1) as its main target layer. However, the systematic study on the geological and geochemical characteristics of K2qn1 in the sag has not been carried out. Taking the core samples from the SYY1 well covering the whole K2qn1 as the main study object and concerning some relevant intervals from the SYY1HF well and other earlier wells, petrologic features, organic geochemical characteristics, oil-bearing property, and reservoir characteristics of K2qn1 were analyzed in detail. The results show that the lithology of K2qn1 is mainly dark mudstone genera accounting for more than 90% of the formation thickness with few macrostructural fractures, indicating that K2qn1 developing in deep to semideep lacustrine facies of the Qijia Sag belongs to the typical matrix reservoirs for shale oil. According to lithology features and logging curves, K2qn1 can be divided into three submembers consisting of K2qn11, K2qn12, and K2qn13 from above to below. Compared to the K2qn11 submember, the K2qn12 and K2qn13 submembers obviously are more enriched in shale oil, which is supported by the following three aspects: (i) the average TOC (total organic carbon) values of K2qn11, K2qn12, and K2qn13 are 1.96%, 2.42%, and 2.72%, respectively. The organic matter types of K2qn12 and K2qn13 are mainly type I and type II1, while those of K2qn11 are mainly type II1 and type II2. K2qn1 is at the end of the oil window with a Ro (vitrinite reflectance) average of 1.26%, and the maturity of K2qn12 and K2qn13 is slightly higher than that of K2qn11. (ii) The average OSI (oil saturation index) values of K2qn11, K2qn12, and K2qn13 are 110.54 mg/g, 171.74 mg/g, and 150.87 mg/g, respectively, which all reach the zone of oil crossover. The saturated hydrocarbon of EOM (extractable organic matter) in K2qn12 and K2qn13 is of higher content than that in K2qn11, while it is the opposite for the aromatic hydrocarbon, nonhydrocarbon, and asphaltene, indicating better oil mobility for K2qn12 and K2qn13. The average oil saturation values of K2qn11, K2qn12, and K2qn13 are 24.77%, 32.86%, and 35.54%, respectively. (iii) The intragranular dissolution pores and organic pores in K2qn12 and K2qn13 are more developed than those in K2qn11. The average effective porosity values of K2qn11, K2qn12, and K2qn13 interpreted from NMR logging are 4.88%, 6.26%, and 5.86%, respectively. Based on the above-mentioned analyses, the lower K2qn12 and the upper K2qn13 are determined as the best intervals of shale oil enrichment for K2qn1 vertically in the Qijia Sag. There is a certain horizontal heterogeneity of TOC, S1, and effective porosity in the drilling horizontal section of K2qn1 of the SYY1HF well. Therefore, the lower K2qn12 and the upper K2qn13 in the area with relatively weak horizontal reservoir heterogeneity of the study area should be selected as the preferential targets for shale oil exploration.